Peran Dinas Pemberdayaan Masyarakat dan Desa dalam Penguatan Desa: Refleksi Praktik Pengalaman Lapangan Mahasiswa di Kabupaten Mandailing Natal - Afriza, Nugraha Andi; Rambe, Khoirun; Saleh, Ildan; Mawardi, Mawardi; Pohan, Syaparuddin; Nst, Mhd Fadhlan Zainuddin; Lbs, Siti Hawa; Lubis, Saidah (PELITA NUSA TENGGARA, 2026)
This community service activity was carried out through the Field Experience Practice (PPL) of students from Sekolah Tinggi Agama Islam Negeri Mandailing Natal at the Community and Village Empowerment Agency (PMD), Mandailing Natal Regency, from January 12 to February 13, 2026. The community service aimed to support the strengthening of village governance and empowerment through administrative assistance, financial verification, and facilitation of participatory activities. The methods used were a participatory approach and field observation, including data collection on village development in Panyabungan Subdistrict, verification and validation of village treasurer financial data, management of administrative correspondence, and assistance in the preparation of village development documents. The activities were carried out collaboratively with PMD officials and village officials to ensure suitability with field needs. The results showed that the involvement of PPL students contributed to streamlining administrative processes, improving documentation order, and supporting the process of guidance and coordination between village actors. This activity also provided practical experience for students in understanding the dynamics of village governance firsthand. This community service emphasized the importance of synergy between universities and local governments in strengthening village capacity in a sustainable manner.